Psychological predictors of suicide risk in university students [Predictores psicológicos del riesgo suicida en estudiantes universitarios] (2019)
This work shows the risk factors and psychological predictors associated with suicidal behavior in university students in Manizales and Medellín (Colombia). The sample comprised 1408 students. Plutchik s suicide risk, Beck s despair and depression and Barratt impulsivity scales were used. A suicide risk factor of 23.2% was found. Binary regression analysis shows that depression (OR= 1.2), impulsivity (OR= 1.04), hopelessness (OR= 1.1), suicide attempt (OR= 31.5), mental illness and family suicide attempt (OR= 2.2, OR= 2.1) explain between 41% and 62% of the variance of suicide risk. Through a structural equation modeling analysis, three explanatory models were established that show mental illness and suicide attempt in the family (model 1), impulsivity (model 2), and a history of suicide attempt by the student (model 3) are suicide mediating variables. The greatest total effect occurred in model 3, which explains 62.7% of the variation in suicide risk. © 2019, Fundacion VECA. All rights reserved.